Incontinence and Erectile Dysfunction Following Radical Prostatectomy: A Review - Gerasimos Alivizatos; Andreas Skolarikos (The Scientific World Journal)
Radical prostatectomy remains the treatment of choice for localized prostate cancer in age-appropriate and health-appropriate men. Although cancer control is the most important aspect of a radical prostatectomy, minimization of postoperative morbidity, especially urinary incontinence and erectile dysfunction, is becoming a greater concern. We reviewed recent data available on Medline regarding the incidence, pathophysiology, evaluation, and treatment of incontinence and sexual dysfunction after radical prostatectomy. Health-related quality of life issues have been specifically addressed. Although low incidences of incontinence and erectile dysfunction after radical prostatectomy have been reported in the hands of experienced surgeons, the literature review revealed a great variety, with incontinence rates ranging from 0.3–65.6% and potency rates ranging from 11–87%. Several factors contribute to this wide difference, the most important being the application of a meticulous surgical technique. General and cancer-specific health-related quality of life is not being affected after radical prostatectomy. The incidence of incontinence and erectile dysfunction is higher after radical prostatectomy when compared to the incidence observed when other therapies for localized prostate cancer are applied. However, the majority of the patients undergoing radical prostatectomy would vote for the operation again. Today, avoidance of major complications after radical prostatectomy depends mostly on a high-quality surgical technique. When incontinence or erectile dysfunction persists after radical prostatectomy, the majority of the treated patients can be managed effectively by various methods.